MicroRNA‐206 prevents the pathogenesis of hepatocellular carcinoma by modulating expression of met proto‐oncogene and cyclin‐dependent kinase 6 in mice. Issue 6 (30th October 2017) - Wu, Heng; Tao, Junyan; Li, Xiaolei; Zhang, Tianpeng; Zhao, Lei; Wang, Yao; Zhang, Lei; Xiong, Jun; Zeng, Zhi; Zhan, Na; Steer, Clifford J.; Che, Li; et al.
Abstract : Hepatocellular carcinoma (HCC) is one of the most lethal cancers worldwide, and therapeutic agents for this malignancy are lacking. MicroRNAs play critical roles in carcinogenesis and present tremendous therapeutic potential. Here, we report that microRNA‐206 is a robust tumor suppressor that plays important roles in the development of HCC by regulating cell‐cycle progression and the cMet signaling pathway. MicroRNA‐206 was underexpressed in livers of two HCC mouse models, human individuals bearing HCC, and human HCC cell lines. Combining bioinformatic prediction and molecular and cellular approaches, we identified cMET (Met proto‐oncogene), cyclin D1 ( CCND1 ), and cyclin‐dependent kinase 6 ( CDK6 ) as functional targets of microRNA‐206. By inhibiting expression of cMET, CCND1, and CDK6, microRNA‐206 delayed cell‐cycle progression, induced apoptosis, and impaired proliferation of three distinct human HCC cell lines. Systemic administration of microRNA‐206 completely prevented HCC development in both cMyc and V‐Akt murine thymoma viral oncogene homolog 1/neuroblastoma RAS viral oncogene homolog (AKT/Ras) HCC mice, whereas 100% of control mice died from lethal tumor burdens. Conversely, reintroduction of cMet or Cdk6 into livers of cMyc and AKT/Ras HCC mice recovered growth of HCC inhibited by microRNA‐206. These results strongly suggested that cMet and Cdk6 were two functional targets that mediated the inhibitory effect of microRNA‐206 on the development of HCC. MicroRNA‐206 overexpression demonstrated a profound therapeutic effect on HCC in xenograft and cMyc HCC mice. Conclusion: In summary, this study defines a potentially critical role of microRNA‐206 in preventing the growth of HCC and suggests its use as a potential therapeutic strategy for this malignancy. (Hepatology 2017;66:1952–1967)